Les firmes multinationales face au risque climatique : sauver le capital en sauvant la terre ? - Mathias Lefèvre (Éditions en environnement VertigO, 2004)
Climate change calls into question the activities and practices of numerous economic actors. Trying to face the issue, states have engaged in a prevention process. This process stimulated the reaction of major multinational corporations, who constitute important and powerful actors in the dynamics of world capitalism. They have either try to annihilate or to control the institutional process. Engines of contemporary capitalism, fossil fuels’ producers and big consumers are at the heart of the issue. Seen by some of them as a strategic stake and a potential source of economic opportunities, climate change is the place of battles for new markets between rival firms. But the issue can also be read like the place of a larger battle, between firms and critical elements of the society, where what is at stake is the transformation of existing social structures.